Pth Moment Exponential Stability of Impulsive Stochastic Neural Networks with Mixed Delays. (11th December 2012) - Li, Xiaoai; Zou, Jiezhong; Zhu, Enwen
Abstract : This paper investigates the problem of p th moment exponential stability for a class of stochastic neural networks with time-varying delays and distributed delays under nonlinear impulsive perturbations. By means of Lyapunov functionals, stochastic analysis and differential inequality technique, criteria on p th moment exponential stability of this model are derived. The results of this paper are completely new and complement and improve some of the previously known results (Stamova and Ilarionov (2010), Zhang et al. (2005), Li (2010), Ahmed and Stamova (2008), Huang et al. (2008), Huang et al. (2008), and Stamova (2009)). An example is employed to illustrate our feasible results.